Hybrid Solid Polymer Electrolyte From Diapers As Separator For Electrochemical Double Layer Capacitor (EDLC) - Hashim M.A.; Mahmud N.A.C.; Sazali N.E.S.; Hamdan E.; Yahya M.A.; Suhaimi S.; Nadhrah Md Yatim; Che Wan Zanariah Che Wan Ngah (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS